2014
DOI: 10.2478/ep-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of concealed information with of the P300 potential amplitude analysis

Abstract: Studies that make use of the bioelectric activity of the brain and falling back on the EEG are presented as an alternative to classical polygraph examinations, especially those that make use of the Guilty Knowledge Tests/Concealed Information Tests (GKT/CIT). Th eir main purpose is detection of concealed information through the analysis of the bioelectric activity of the brain in response to presented stimuli. Th e article aims at elucidating the main questions concerning the detection of concealed information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Barber, Rajaram, and Aron () and Barber, Harris, and Rajaram () found that the recognition rates of two participants were reduced after encoding the information collaboratively. As noted above, P300‐based CIT basically measures the recognition of crime‐related information (Rosenfeld, ; Wojciechowski, ). So, one might suggest that the P300 amplitude elicited by probe will be lessened if the guilty information is encoded collaboratively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barber, Rajaram, and Aron () and Barber, Harris, and Rajaram () found that the recognition rates of two participants were reduced after encoding the information collaboratively. As noted above, P300‐based CIT basically measures the recognition of crime‐related information (Rosenfeld, ; Wojciechowski, ). So, one might suggest that the P300 amplitude elicited by probe will be lessened if the guilty information is encoded collaboratively.…”
Section: Introductionmentioning
confidence: 99%
“…P300, a component of ERP, can reflect the recognition process (Rugg & Coles, 1995;Rugg & Curran, 2007;Vilberg, Moosavi, & Rugg, 2006). Our protocol uses P300 amplitude to measure the recognition difference of probe stimulus versus irrelevant stimuli so as to detect concealed information regarding an investigated crime (Hu, Bergstrom, Bodenhausen, & Rosenfeld, 2015;Meixner & Rosenfeld, 2014;Rosenfeld, 2011;Wojciechowski, 2014). Many CITbased research studies generate the guilty information by implementing a mock crime situation, for instance, burglary or theft of a piece of jewelry from an area that is prohibited for trespassing (Hu et al, 2015;Visu-Petra, Miclea, Buş, & Visu-Petra, 2014;Winograd & Rosenfeld, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the interest in using EEG examinations for lie detection (see below) has been on the rise again in the wake of the discovery of the P -300 wave (Wojciechowski 2014).…”
Section: Attempts At Lie Detection By Observing Changes In Electroencmentioning
confidence: 99%